Gated single-photon emission computed tomography myocardial perfusion imaging phase analysis as an imaging biomarker for mortality prediction in heart failure patients undergoing cardiac resynchronization therapy. Issue 9 (13th May 2021) - Bazzy, Jimmy; Gadiyaram, Varuna; Nguyen, Brian J.; Birgersdotter-Green, Ulrika; Hoh, Carl K.; Obrzut, Sebastian
Abstract : Objective: Cardiac resynchronization therapy (CRT) reduces morbidity and mortality in heart failure patients. The purpose of this study was to assess the value of gated myocardial perfusion single-photon emission computed tomography (GMPS) phase analysis for predicting survival in heart failure patients undergoing CRT. Methods: This retrospective cohort study evaluated heart failure patients who underwent GMPS prior to CRT. Phase histogram bandwidth (PHB) and phase SD (PSD) were calculated using GMPS data. Cox proportional hazards model was used to identify independent predictors of overall survival (OS). Results: A total of 35 patients (age 65.1 ± 13.3, 27 men and 8 women), who were followed for mean of 4.1 ± 2.9 years, were enrolled in the study. PSD of greater than 45° was found to be an independent predictor of poor OS (hazard ratio = 12.63, P  = 0.011) when compared with age (hazard ratio = 1.00, P  = 0.922), gender (hazard ratio = 0.31, P  = 0.155), NYHA class (hazard ratio = 0.45, P  = 0.087), QRS duration greater than 150 ms (hazard ratio = 2.38, P  = 0.401), pre-CRT left ventricular ejection fraction (LVEF) (hazard ratio = 0.95, P  = 0.175) and etiology of heart failure (hazard ratio = 1.42, P  = 0.641). Furthermore, PHB greater than 140° was also found to be an independent predictor of poor OS (hazard ratio = 5.63, P  = 0.040) when compared with age, gender, NYHA class, QRS duration greater than 150 ms, pre-CRT LVEF and etiology of heart failure. Conclusions: PSD and PHB, measured by GMPS, may serve as biomarkers for the prediction of survival in patients undergoing CRT.